2011
DOI: 10.1287/msom.1100.0317
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Component Commonality in Product Assortment Decisions

Abstract: W e consider a firm that produces multiple variants of a product. Products are assembled using a combination of common and dedicated components. We characterize the optimal assortment and derive the optimal inventory levels for the common and dedicated components under various bill-of-material configurations. We investigate the effect of commonality on product variety and compare its benefits under different demand characteristics. Commonality always leads to increased profits, but its effect on the level of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…A simulation model t h a t a l l o w s e x a m i n i n g t h e d y n a m i c s b e t w e e n modularization, innovation, and performance in complex systems was developed [125]. Other study investigated the effect of commonality (common components/modules) in relation to product variety and compared their benefits under different demand characteristics [126]. Gupta and Roth [127] discussed the contributions of Martin K. Starr to production and operations management, which include the seminal approach of modular production, described in Starr [8].…”
Section: Studies Of Brazilian Journals and Other Investigationsmentioning
confidence: 99%
“…A simulation model t h a t a l l o w s e x a m i n i n g t h e d y n a m i c s b e t w e e n modularization, innovation, and performance in complex systems was developed [125]. Other study investigated the effect of commonality (common components/modules) in relation to product variety and compared their benefits under different demand characteristics [126]. Gupta and Roth [127] discussed the contributions of Martin K. Starr to production and operations management, which include the seminal approach of modular production, described in Starr [8].…”
Section: Studies Of Brazilian Journals and Other Investigationsmentioning
confidence: 99%
“…Under the assumption that all variants have an identical newsvendor ratio, van Ryzin and Mahajan demonstrated that the optimal assortment should consist of a certain number of the most popular variants. Subsequent research extended the analysis to study how the retailer's assortment decisions could be affected by component commonality (Bernstein et al., ), category captainship (Kurtulus & Nakkas, ), or endogenous pricing (Maddah & Bish, ; Aydin & Porteus, ). Several other studies took a different route by relaxing the assumption of an identical newsvendor ratio.…”
Section: Related Literaturementioning
confidence: 99%
“…We assume two components or sub-assemblies are required in the product's assembly process, which is commonly considered to simplify the problem in the assembly system (see Bernstein, Kök, and Xie 2011;Gurnani and Gerchak 2007;Thomas, Warsing, and Zhang 2009;Yano 1987). The requested quantity of each component for the final product is assumed to be one unit.…”
Section: Problem Description and Notationsmentioning
confidence: 99%